EFL Students' Learning Motivation and Descriptive Essay in the Context of Blended Learning Design - Apoko, Tri Wintolo; Chong, Su Li (JEELS (Journal of English Education and Linguistics Studies), 2024)
EFL students should consider writing motivation in a blended learning (BL) framework. Previous studies have discussed findings related to whether motivations can make students write essays better. Few studies have examined descriptive essay learning motivation in BL design. This study examined EFL students' learning motivation on descriptive essays in BL designs and their perceptions on essay writing motivation. The respondents were 32 EFL students in one reputable private university in Jakarta, Indonesia. This study was a correlational survey. The data was collected using a Likert-scale questionnaire and a descriptive essay writing test with a scoring rubric developed by Oshima & Hogue (2006). The result showed that there was a positive and significant contribution of learning motivation on descriptive essay in a BL design. It also showed that learning motivation contributed 12.9% to the students’ descriptive essay writing skill. In addition, most students felt happy to practice writing in a BL design. Thus, it is inferred that EFL students could perform their essay writing quality in a BL design when they had strong learning motivation which included the intrinsic and extrinsic domains.